Efficiency Analysis Of Jetor Engine Fuel Requirements In Rice Field Plowing Activities In Sigumpar Village - Kevin Manullang; Juli Siagian; Francis Simbolon; Joel Sidabutar; Arnold Hutagalung; Tambos Sianturi; Herna Sianipar (International journal of technology and education research, 2026)
Land preparation is the most crucial initial step in successful rice cultivation, but it requires significant operational costs, particularly fuel consumption. This study aims to analyze the fuel efficiency and operating capacity of a hand tractor (jetor) on a 7,200 m2 rice field in Sigumpar Village. The research method used was direct field observation, measuring parameters such as working time, cultivated area, and fuel consumption. The results showed that to cultivate 7,200 m2 of land, the jetor required a total operating time of 9 hours and consumed 9.5 liters of diesel fuel. The average specific fuel consumption was 1.32 liters per 1,000 m2, with an Effective Working Capacity (ECC) of 800 m2/hour. The analysis showed a field efficiency level of 80%. The main factors contributing to the 20% efficiency loss were turning time at the edge of the field, overlapping tracks, and clay soil conditions that cause wheel slippage. This study concludes that the use of jetor machines in Sigumpar Village is quite optimal, but efficiency can still be improved through regular plowshare maintenance and more precise track pattern management